2015
DOI: 10.1002/adfm.201501688
|View full text |Cite
|
Sign up to set email alerts
|

“Layer‐Filter Threshold” Technique for Near‐Infrared Laser Ablation in Organic Semiconductor Device Processing

Abstract: Although conventional laser ablation (CLA) method has widely been used in patterning of organic semiconductor thin films, its quality control still remains unsatisfied due to the ambiguous photochemical and photothermal processes. Based on industrial available near‐infrared laser source, herein, a novel “layer‐filter threshold” (LFT) technique is proposed, which involves the decomposition of targeted “layer‐filter” and subsequent explosive evaporation process to purge away the upper layers instead of layer‐by‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In order to obtain the high-performance OTFT array, the thermal effect must be reduced as much as possible. It should be pointed out that a laser at the visible region was previously reported for organic layer ablation, as the absorption at the near-infrared of organic polymers is intrinsically weak. Thus, most of the laser absorption and energy transfer was confined within the Ag layer under the irradiation of the laser with 1064 nm wavelength. Meanwhile, the thermal conductivity of organic semiconductors was relatively low to the metal thermal conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…In order to obtain the high-performance OTFT array, the thermal effect must be reduced as much as possible. It should be pointed out that a laser at the visible region was previously reported for organic layer ablation, as the absorption at the near-infrared of organic polymers is intrinsically weak. Thus, most of the laser absorption and energy transfer was confined within the Ag layer under the irradiation of the laser with 1064 nm wavelength. Meanwhile, the thermal conductivity of organic semiconductors was relatively low to the metal thermal conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…The same can be said about procedures developed in the organic photovoltaics (OPVs) field. Many recent developments to optimize laser processing of PV modules based on organic semiconductors have been reported in the literature, which should enable the high‐throughput manufacture of these thin‐film modules, whilst ensuring high geometrical aperture ratios . Inactive or dead areas as low as 200 μm have been reported, with module geometrical aperture ratios larger than 90–97%.…”
Section: Discussionmentioning
confidence: 99%
“…Femtosecond laser (fs) processing is a universal mask-free technology which can be used to fabricate fine micro/nanostructures with extremely high resolution in numerous material systems, providing impressive advances in materials science, industrial and medical fields. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Recently, Guo et al showed a facilely fs laser patterning of polymer OSC thin films by taking advantage of the ablation effect of fs laser irradiation. 34 Furthermore, this novel fs-laser patterning strategy was demonstrated to be able to create an organic field-effect transistor (OFET) array with a high device density of 6250 cm À2 on soft substrates and the resulting OFET array showed promising potential in image sensor applications.…”
Section: Introductionmentioning
confidence: 99%